Women in Chinsapo, Malawi: vulnerability and risk to HIV/AIDS - Jayati Ghosh; Ezekiel Kalipeni (Taylor & Francis Group, 2005)
Malawi, a very poor country located in southern Africa, is no exception to the growing trend and severity in HIV prevalence. By the end of 2003 there were 900 000 adults and children in Malawi living with HIV/AIDS. Adult prevalence was estimated to be 15%, which is higher than the 7.1% average rate for sub-Saharan Africa. In order to understand the spread of HIV/AIDS it is imperative to address the economic, social, cultural, and political issues that impact on women's contraction and spread of the virus. We do so in this paper by critically examining the gendered context of HIV/AIDS with reference to Malawi. The theoretical framework for this research focuses on poverty, gender relations, regional migration patterns, and global economic changes which place women in highly vulnerable situations. The study was conducted in a low-income area in Lilongwe, the capital city of Malawi. In 2003 and 2004, 60 randomly selected women who lived in a low socioeconomic residential area completed a structured interview on issues concerning individual economic situations, marriage history, fertility, family planning and social networks, gender, sexual partnerships, and HIV/AIDS. Focus group interviews were also conducted with an additional 20 women. The results of our study indicate that the rising epidemic among women in Malawi is firstly driven by poverty which limits their options. Secondly, gender inequality and asymmetrical sexual relations are basic to spreading HIV/AIDS among women. Thirdly, in spite of their awareness through media and health care professionals, women are unable to protect themselves, which further increases their vulnerability.